Pelindungan Hukum terhadap Saham yang Diperjualbelikan oleh Investor Melalui Transaksi Online - Siregar, Emiel Salim; Manasar, Andrew; Sembiring, Roy Imanta; Juwanti, Tika; Barus, Tri Vena Agintha; Panjaitan, Sofyan; Adelia, Cici (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The rapid development in the capital market in the technology that currently exists affects the conduct of transactions in the capital market on buying and selling which is carried out directly using online media, the intermediary system in question is that provided by securities trading on electronic media referred to as the internet in an application developed In today's digital era, it is possible to access and trade shares directly using smartphone electronic devices. This research uses normative law research, namely: legal research that examines written law from various aspects, such as aspects of theory, history, philosophy, comparison, structure, composition, scope, material, and consistency of general and article explanations. by article, the formality and binding power of a law, the language used, as well as institutions and legal subjects Keywords: Legal Protection, Buying and Selling Shares, Investors, Online Transactions